Evolution of the Land Plant Exocyst Complexes - Cvrckova, Fatima; Grunt, Michal; Bezvoda, Radek; Hala, Michal; Kulich, Ivan; Rawat, Anamika; Zarsky, Viktor (Frontiers in Plant Science, 2012)
Exocyst is an evolutionarily conserved vesicle tethering complex functioning especially in the last stage of exocytosis. Homologs of its eight canonical subunits -Sec3, Sec5, Sec6, Sec8, Sec10, Sec15, Exo70 and Exo84 - were found also in higher plants and confirmed to form complexes in vivo, and to participate in cell growth including polarized expansion of pollen tubes and root hairs. Here we present results of a phylogenetic study of land plant exocyst subunits encoded by a selection of completely sequenced genomes representing a variety of plant, mostly angiosperm, lineages. According to their evolution histories, plant exocyst subunits can be divided into several groups. The core subunits Sec6, Sec8 and Sec10, together with Sec3 and Sec5, underwent few, if any fixed duplications in the tracheophytes (though they did amplify in the moss Physcomitrella patens), while others form larger families, with the number of paralogs ranging typically from two to eight per genome (Sec15, Exo84) to several dozens per genome (Exo70). Most of the diversity, which can be in some cases traced down to the origins of land plants, can be attributed to the peripheral subunits Exo84 and, in particular, Exo70. As predicted previously, early land plants (including possibly also the Rhyniophytes) encoded three basal Exo70 paralogs which further diversified in the course of land plant evolution. Our results imply that plants do not have a single "Exocyst complex" – instead, they appear to possess a diversity of exocyst variants unparalleled among other organisms studied so far. This feature might perhaps be directly related to the demands of building and maintenance of the complicated and spatially diverse structures of the endomembranes and cell surfaces in multicellular land plants.